Elements of family style : elegant spaces for everyday life - Gates, Erin T (Atria Books, 2019)
Loved by her readers for her chic interior designs and frank and funny revelations about life behind the scenes of her picture-perfect blog, bestselling author and designer Erin Gates presents a new book about how to live stylishly amidst the chaos of daily family life. Throughout her career designing homes for families of all kinds all over the country, Erin has always maintained that living with children and pets does not mean that you have to forego nice things. This uniquely personal and practical guide will explain how to create a home that makes you proud and reflects your own style while also being durable, safe, and comfortable for children. It focuses on the spaces families share, those that are dedicated to the kids, and the oft-forgotten retreats for parents.